Customers Relationship Considerations in Hotels Belonging to an International Chain - Cosma, Smaranda; Fleșeriu, Cristina; Bota, Marius (International Journal of Economic Practices and Theories, 2015)
The best ranked hotel chains possess more than 1/3 of the world’s accommodation capacities. International hotel groups have penetrated the Romanian market and even if their presence is relatively small, the weight they possess is significant. The development of relationships with customers could be considered empathic to the hotel industry and it is significant because the hotel sector is highly competitive. The main purpose of the study is to identify the approach to their customers and the loyalty methods used by the hotels in Romania belonging to an international hotel chain. A descriptive research, applying an interview based on a questionnaire was performed. The research reveals that the communication with the clients is made mostly direct, but also by using the hotels’ own website. The hotels own databases with clients. The structure of the database allows them to personalize the offered services, what attracts an increasing degree of customer satisfaction. The strategies and the policies used to retain clients are established mutually, taking into consideration the proposals made by the international chain but also the hotels’ ideas.